A Wideband Printed Antenna for Covering Major Cellular Bands with a C- Shaped Patch - Misra, P.; Tripathy, A. (International Journal of Engineering and Technology, 2012)
In this paper the design of a new multistandard antenna is proposed suitable for major cellular bands. A C-shaped radiator with a microstrip feed line is proposed which supports major cellular communication band like AWS, DCS, DECT, PCS, PHS, 3G, UMTS, DSR, Wi-Bro, ISM, and DMB in the range of 1.7- 2.9 GHz. The designed antenna is simulated using CST Microwave Studio to achieve such wide frequency coverage. The simulation results of the designed structure in terms of return loss, VSWR and radiation pattern are presented.